2017
DOI: 10.3390/su9040556
|View full text |Cite
|
Sign up to set email alerts
|

Are Consumers Willing to Pay More for a “Made in” Product? An Empirical Investigation on “Made in Italy”

Abstract: Abstract:The paper aims to explore consumer behavior towards "Made in" products in order to determine the associated quality and value-attributes related to the purchasing intention of consumers. In particular, the article presents the comments and results deriving from an empirical investigation on "Made in Italy". The research questions addressed are: (1) Does recognition really exist in terms of qualitative characterization of "Made in Italy" products? And if yes; (2) Does willingness to pay a "premium pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The answers collected from the discussion are graphically depicted in Figure 2 using word clouds. It is a visual representation of text data, widespread for reporting qualitative data (Cappelli et al, 2017). The most frequent words appeared to represent the key concerns of consumers while purchasing dairy products, as it has demonstrated from the word cloud.…”
Section: Purchasing Behaviour 41 Consumers' Concerns While Purchasing Dairy Productsmentioning
confidence: 99%
“…The answers collected from the discussion are graphically depicted in Figure 2 using word clouds. It is a visual representation of text data, widespread for reporting qualitative data (Cappelli et al, 2017). The most frequent words appeared to represent the key concerns of consumers while purchasing dairy products, as it has demonstrated from the word cloud.…”
Section: Purchasing Behaviour 41 Consumers' Concerns While Purchasing Dairy Productsmentioning
confidence: 99%
“…Researches on the image of the "Made in Italy" brand have demonstrated the real significance of the brand image, placing it in the top position for brand awareness in most countries (Cappelli et. al, 2017).…”
Section: Country Of Originmentioning
confidence: 99%
“…The paper fills a gap in the literature, since there are few references for an understanding of the real value of "Made in Italy" expressed in terms of orientation towards "Made in Italy" products, and there are scant quantifications of the willingness to pay for "Made in Italy" products. It has emerged that there is both a robust recognition of "Made in Italy" products in terms of high-quality, and a manifest willingness to pay a price increase of 10% to 30% (Cappelli et al, 2017). For this reason, the objective of the present study is to expand the field survey by introducing the concept of "innovation", and seeking to verify whether, and if so to what extent, consumers perceive the innovation as an element of identification of "Made in Italy" products, in order to analyze the propensity and the consumer attitude towards such products.…”
Section: Introductionmentioning
confidence: 99%
“…The main results obtained so far by Cappelli et al (2016Cappelli et al ( , 2017Cappelli et al ( , 2019 [1][2][3] have clearly shown that Made in Italy products not only represent a well-defined conceptual category in the minds of Italian consumers, but that there is a premium price for Made in Italy products in the studied sectors (food, furniture, textile/clothing, mechanical automation), within a range of 10-30% depending on a sector. The results obtained so far [3] have shown that the premium price is generally higher for Made in Italy products in the food sector.…”
Section: Introductionmentioning
confidence: 99%